Pemberian Sesi Konseling untuk Mengurangi Beban Kerja Mental Pegawai Departemen Sumber Daya Manusia PT X - Nurfika Nabiya; Asri Rejeki (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This report discusses the mental workload of employees in the Human Resources (HR) Department of PT X in Gresik, which is an important concern in the context of employee productivity and well-being. The purpose of this research is to identify the factors that influence mental workload and provide recommendations for improvement. The research methods used include observation, interviews, and the distribution of questionnaires to all HR employees, with the NASA TLX approach to measure the level of mental workload. The research sample consists of eight employees selected based on the questionnaire results. The data analysis technique was carried out by identifying factors that influence mental workload and evaluating the effectiveness of interventions through counseling sessions. The research results show that mental workload is influenced by high job demands, lack of team support, and poor communication. The counseling sessions conducted had a positive impact on employee stress management. The novelty of this research lies in its focus on mental workload within the organizational context, as well as recommendations for more humane policies. The implications of this research highlight the importance of paying attention to employees' mental well-being to enhance productivity and create a healthier work environment. This research is expected to serve as a reference for management in designing strategies that support employee well-being.